3(6+2x)=4(3x+12)

Simple and best practice solution for 3(6+2x)=4(3x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6+2x)=4(3x+12) equation:



3(6+2x)=4(3x+12)
We move all terms to the left:
3(6+2x)-(4(3x+12))=0
We add all the numbers together, and all the variables
3(2x+6)-(4(3x+12))=0
We multiply parentheses
6x-(4(3x+12))+18=0
We calculate terms in parentheses: -(4(3x+12)), so:
4(3x+12)
We multiply parentheses
12x+48
Back to the equation:
-(12x+48)
We get rid of parentheses
6x-12x-48+18=0
We add all the numbers together, and all the variables
-6x-30=0
We move all terms containing x to the left, all other terms to the right
-6x=30
x=30/-6
x=-5

See similar equations:

| 36x+18+5=2 | | 17/43=x/301 | | 70/20=n/195 | | y-1+5=2 | | 15x=85/550 | | 20/70=n/195 | | |y-1|+5=2 | | 70/20=195/n | | |a+4|=-1 | | (4x+6)-(3x+1)= | | (1/5)-3b=5 | | 5=t3 | | 5n+65n=37n | | 7y^2=28. | | 6(2-d)=9(-d4) | | -2.5x-4.25x=35.1 | | D(2D+4)y=0 | | -3(2x+4)=9 | | 4x(x^2+2)=9 | | -8(5x-4)+8=5x | | 0.01x+0.1(x+20,000)=2220 | | -8(5x-4)+8=5x | | 601/12.9=1250/n | | 5n+4+3n=36 | | {4}{3}x{1}{3}=x+7 | | -3x+7-2x=52 | | (2x+3x)+62=180 | | (x+5)(x-2=0 | | D=(m-64)2 | | 0.3x+2=5.6 | | 7t-21=2t-18+2R | | t1=2(1)+4 |

Equations solver categories